Design and reanalysis of pile cap with four pile group due to pile failure - Nadzirah Mohd Fozi, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2017